EFFECTIVENESS OF THE FERMENTATIVE EXTRACT OF Lactobacillus acidophilus AS ANTIMICROBIALS AGAINST Aeromonas hydrophila - Akter, Mst Nahid; Hashim, Roshada; Sutriana, Amalia; Mohd Nor, Siti Azizah (Universitas Syiah Kuala, 2018)
The purpose of this study was to evaluate the in vitro and in vivo antimicrobial activity of the commercial Lactobacillus acidophilus (L. acidophilus) cells and cell free extract against Aeromonas hydrophila (A. hydrophila). The in vitro method was carried out using well diffusion method. For in vivo evaluation, the effect of L. acidophilus on the survival rate of Pangasianodon hypophthalmus (P. hypophthalmus) infected with A. hydrophila was evaluated. The well diffusion method showed a significant inhibition ability of L. acidophilus cells against A. hydrophila compared to the cell free extract. The inhibition diameters obtained with cells and cell free extract were 17.23 mm and 15.17 mm, respectively. P. hypophthalmus injected with L. acidophilus cells and cell free extract following challenged with A. hydrophila cells showed survival rate of 70% and 60% respectively, at 2-week post challenged. The gas chromatography-mass spectrophotometry (GC-MS) result revealed that a diverse of compounds was detected in both the L. acidophilus cells and cell free extract, among them the most abundant component was pyrrolo[1,2-a]pyrazine-1,4-dione, hexahydro-3-(2-methylpropyl), which showed a promising anticancerous activity and might be played a significant role in the recovery of the infectious P. hypophthalmus. The current study revealed that both cells and cell free extract of L. acidophilus have antimicrobial activity against A. hydrophila.